DIPLOMASI BUDAYA KOREA SELATAN TERHADAP INDONESIA MELALUI DRAMA KOREA BERTEMA KELUARGA TAHUN 2021-2023 - Adisti, Raisa; Konety, Neneng (Indonesian Journal of International Relations, 2025)
This article analyzes South Korea's cultural diplomacy towards Indonesia through family-themed Korean dramas in 2021-2023. Family-themed Korean dramas play a role in building a positive image of South Korea and strengthening cultural ties between the two countries. This article uses Patricia Goff's theory of cultural diplomacy, namely connection, consistency, and innovation, in the production and distribution of family-themed Korean dramas. The method used is qualitative with literature study, interviews, and content analysis. The results of the research show that family-themed Korean dramas not only convey universal family values, but also introduce Korean culture to Indonesian audiences, including language, food, and traditions. Family-themed Korean dramas have succeeded in increasing understanding of Korean culture in Indonesia, creating a consistent positive image, and innovating in digital distribution. This success strengthens bilateral relations between South Korea and Indonesia through an effective cultural diplomacy strategy.